In Your Eyes I See My Words Homilies and Speeches from Buenos Aires, Volume 3: 2009-2013 - Franziskus Papst 1936-2025 (Fordham University Press, 2020)
In Your Eyes I See My Words, Volume 3 brings together the homilies and speeches of Archbishop Cardinal Jorge Mario Bergoglio from 2009 through his election as Pope Francis on March 13, 2013. Taken together, all three volumes present with remarkable clarity his theological, educational, and pastoral vision for the Church that was shaped far from Europe and North America, and in the tumultuous years of Argentina's political and economic struggles. These writings provide an intimate glimpse into the theological, philosophical, scientific, and cultural-educational currents that forged the steady, loving, and nurturing hands with which Bergoglio guided the Church in Buenos Aires. Those very same hands have now done the same for the Church from Rome, a Church rocked by financial and moral scandals, and a world shaken by the first global pandemic in a century.
Keywords: Geschichte 2009-2013; RELIGION / Theology; Seelsorge; Buenos Aires